Towards Lagrangian formulations of mixed-symmetry higher spin fields on AdS-space within BFV-BRST formalism - Reshetnyak, A. A. (Physics of particles and nuclei, 2010)
The spectrum of superstring theory on the AdS 5 × S 5 Ramond-Ramond background in tensionless limit contains integer and half-integer higher-spin fields subject at most to two-rows Young tableaux Y ( s 1 , s 2 ). We review the details of a gauge-invariant Lagrangian description of such massive and massless higher-spin fields in anti-de-Sitter spaces with arbitrary dimensions. The procedure is based on the construction of Verma modules, its oscillator realizations and of a BFV-BRST operator for non-linear algebras encoding unitary irreducible representations of AdS group.